Study of Educational Problems Based on Aspects of Equity, Efficiency, Quality, and Relevance - Miftakhul Firman Ferdiansyah Efendi (Yayasan Nurul Yakin Bunga Tanjung, 2023)
This research is a qualitative descriptive study that aims to describe educational problems based on four aspects, namely equity, efficiency, quality, and relevance. The research was conducted at SMAN 1 Sumberpucung, Malang Regency. Data collection was done by interview, observation, and documentation methods. Data triangulation was carried out based on data obtained from the three methods which verify and complement each other. Data analysis was carried out using the Miles and Huberman method, namely the stages of data reduction, data presentation, and drawing conclusions. The results showed that at SMAN 1 Sumberpucung there were several problems, both in terms of equity, efficiency, quality, and relevance. In the aspect of equity, there are several problems, namely, (a) at first there were problems in recruiting prospective students who excel, (b) there were students who withdrew from school, and (c) the implementation of remedial measures was not in accordance with the difficulties experienced by students. The problem in the efficiency aspect is that students with low abilities do not get special services. In terms of quality, schools still do not have a separate laboratory. And in the aspect of relevance, the learning carried out still does not use a scientific approach.